If it bleeds [compact disc, unabridged] : new fiction - King, Stephen, 1947- (Audioworks, Simon & Schuster Audio, 2020)
A collection of four novellas includes the title story in which Holly Gibney of the Bill Hodges trilogy and "The Outsider" struggles to face her fears and another possible outsider.